2019
DOI: 10.1371/journal.pone.0221721
|View full text |Cite
|
Sign up to set email alerts
|

High A20 expression negatively impacts survival in patients with breast cancer

Abstract: Background A20 protein has ubiquitin-editing activities and acts as a key regulator of inflammation and immunity. Previously, our group showed that A20 promotes tumor metastasis through multi-monoubiquitylation of SNAIL1 in basal-like breast cancer. Here, we investigated survival outcomes in patients with breast cancer according to A20 expression. Patients and methods We retrospectively collected tumor samples from patients with breast cancer. Immunohistochemistry (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Previous studies have suggested that effector T cell-derived IFNγ contributes to high levels of PD-1 expression in the tumor microenvironment ( 42 ); CCL2 attracts monocytes, increases the number of tumor-associated macrophages and promotes angiogenesis in breast cancer ( 43 ). Overexpression of CXCL10 is considered to be a favorable prognostic factor in TNBC ( 44 ), and high levels of TNFAIP3 expression are correlated with poor overall survival in HER2 + breast cancer and TNBC ( 45 ). We observed a close relationship between these hub genes and neutrophil infiltration in breast cancer tissue, suggesting that IL-17 cytokines attract and activate neutrophils by stimulating the production of neutrophilic chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that effector T cell-derived IFNγ contributes to high levels of PD-1 expression in the tumor microenvironment ( 42 ); CCL2 attracts monocytes, increases the number of tumor-associated macrophages and promotes angiogenesis in breast cancer ( 43 ). Overexpression of CXCL10 is considered to be a favorable prognostic factor in TNBC ( 44 ), and high levels of TNFAIP3 expression are correlated with poor overall survival in HER2 + breast cancer and TNBC ( 45 ). We observed a close relationship between these hub genes and neutrophil infiltration in breast cancer tissue, suggesting that IL-17 cytokines attract and activate neutrophils by stimulating the production of neutrophilic chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observe upregulated expression levels of CXCR4, A20, and Snail1 in basal-like TNBC cells, suggesting that these proteins might be involved in the stabilization of Snail1. A20 is known to promote the stability of Snail1 through its monoubiquitination of Snail1 [ 45 , 57 ]. Nuclear pS473-Akt is an active serine kinase that stabilizes Snail1 through the inactivating phosphorylation of nuclear GSK-3β on S9.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth to be noted that the function of TNFAIP3 varies, as a tumor enhancer or suppressor, depending on different cancer context 29,30,32 . For example, TNFAIP3 is overexpressed in breast cancer, associated with breast cancer aggressiveness and poor prognosis of breast cancer patients 29 . TNFAIP3 mediates TNF-α promoted triple negative breast cancer aggressiveness, and its absence leads to cell apoptosis 33 .…”
Section: Discussionmentioning
confidence: 99%